INFLUENCE OF LEADERSHIP AND PERFORMANCE WORK THROUGH DISCIPLINE OFFICE FACILITIES IN THE VILLAGE IN DISTRICT DISTRICT ENTIRE STOCK SINJAI - Idham Idham; agussalim Harrang; Fitriani Fitriani (Universitas Muhammadiyah Makassar, 2021)
This study aims to determine and analyze the influence of leadership and work discipline on performance through office facilities at village officials in Sinjai Borong District, Sinjai Regency. This type of research is quantitative research using a questionnaire as a source of data collection. This study uses the SmartPLS analysis technique. The results of this study indicate that: 1) Leadership has a significant positive effect on office facilities, 2) Work discipline has a significant positive effect on performance, 3) Leadership has a significant positive effect on performance, 4) Work discipline has a significant positive effect on performance, 5) Office facilities are significant positive effect on performance, 6) Leadership has a significant indirect effect on performance through office facilities, 7) Work discipline has no significant indirect effect on performance through office facilities